Current and Future Treatments, Prevention, Diagnosis on Retinoblastoma - Singh Chouhan, Ashwin; Khan, Sohail (Asian Journal of Pharmaceutical Research and Development, 2023)
The most frequent intraocular cancer in children is retinoblastoma. All pediatric patients with retinoblastoma must undergo genetic testing as a crucial part of their treatment. Retinoblastoma can also extend to the brain and spine, among other parts of the body. MRI and CT scans are two imaging procedures that may be used to detect retinoblastoma. The size and location of the retinoblastoma tumor in your child determine the optimal course of treatment. Chemotherapy is a type of medication that can be used to treat cancer. Chemotherapy can aid in tumor reduction, enabling subsequent therapies like radiation therapy, cryotherapy, or laser therapy to target any remaining cancer cells. Early eye examinations are crucial for diagnosis and care. If detected early, retinal blastoma is frequently treatable. A hereditary mutation may cause retinal tumors (retinoblastoma). External beam radiation therapy, cryotherapy, laser photocoagulation, thermotherapy, brachytherapy, and chemotherapy (intravitreal, intra-arterial, and systemic) are now included in the treatment of retinoblastoma in addition to the damaged globe. Long-term side effects of radiation and chemotherapy in retinoblastoma patients can include secondary cancers.